MISCONCEPTION IDENTIFICATION OF VII CLASS GRADE STUDENTS ON THE SUBJECTS OF MATERIAL AND CHANGE CLASSIFICATION - SRIWATI APRILIANI, SITI; MARTINI (PENSA E-JURNAL: PENDIDIKAN SAINS, 2019)
This research aims to identify understanding of concepts and the level of student misconception in learning about atoms, molecules, elements, compounds and mixtures. The sample in this study were 35 grade VII students at SMP N 17 Surabaya. The method used in this study is the provision of diagnostic tests based on the CRI (Certainty of Response Index) method. The diagnostic test results showed a misconception about identifying the molecular formula of a compound (11.5%), explaining the meaning of elements (50%), identifying examples of elements in daily life (25.7%), explaining the meaning of compounds (14.2% ), identifying compound properties (48.6%), identifying compound samples in daily life (5.7%), identifying mixed properties (2.9%), identifying differences in homogeneous mixtures (2.9%) and heterogeneous, identify examples of homegene and heterogeneous mixtures (20%). The forms of misconceptions found in this study are theoretical and classification misconceptions. Keyword : Misconceptions, misconceptions theoretical and classification misconceptions